Quantum hydrodynamics of strongly coupled electron fluids. - Schmidt, R; Crowley, B; Mithen, J; Gregori, G (2012)
We have extended the classical hydrodynamics formalism to include nonlocal quantum behavior via the phenomenological Bohm potential. We have then solved the quantum hydrodynamics equations to derive an expression for the dynamical structure factor, which describes the density-density correlations in the system. This formalism can be applied to high density strongly coupled electron fluids in the long wavelength domain. We show that at densities above 7×10(25) cm(-3) there are significant differences in the dispersion relation. Future experiments at large laser facilities could provide an experimental test of the theory.